Reporting the 'War on Terror' - Lashmar, Paul (Henry Stewart Talks, 2010)
Reasons for War, Definitions, Al Qaeda, Reasons for terrorism, Global changes in media, Reporting 9/11, Afghanistan, Iraq and Weapons of Mass Destruction, The PR State, US media critique, Academic response, UK reporting of War on Terror, Politicization of intelligence, Hutton Inquiry, Backlash, PR of terror, Home grown terrorism, Post invasion Iraq, Water boarding, torture and rendition, Exceptional journalism, Analysis, Flat Earth News, Key concepts, Media, war and postmodernism, Conclusions
Archived at 2022/04/12